Gambaran Klinikopatologik Lupus Nefritis di RSUP Sanglah Denpasar tahun 2016-2020 - Nariswari, Ida Ayu Ista; Winarti, Ni Wayan; Sriwidyani, Ni Putu; Dewi, I Gusti Ayu Sri Mahendra (Universitas Udayana, 2022)
ABSTRACT Systemic lupus erythematosus (SLE) is one of the most common autoimmune diseases in the community. One of common clinical manifestations of SLE is Lupus Nephritis (LN). The World Health Organization (WHO) notes that there are five million people with lupus in the world and there are 100,000 more new sufferers every year. In Indonesia in 2016 it was reported that 2,166 patients were hospitalized with a diagnosis of SLE and 550 of them died. This study aims to determine the characteristics of LN patients at Sanglah Hospital Denpasar in 2016-2020 based on age, gender, histopathological class (categorized according to ISN/RPS), and proteinuria level and to determine the relationship between proteinuria level and histopathological class and the relationship between age and histopathological class. This research was conducted at the Anatomical Pathology (PA) laboratory of Sanglah Hospital Denpasar in 2021 with a cross-sectional method, using secondary data that available at the PA laboratory of Sanglah Hospital Denpasar, then processed using SPSS ver. 26. The results showed that the total number of LN patients at Sanglah Hospital Denpasar in 2016-2020 was 28 cases. Most cases were found at age range of 26-35 years (11 cases or 39.3%) and most were female (23 cases or 82.1%). The most common proteinuria level found was +3 (8 cases or 28.6%) and the most common histopathological class was class IV (13 cases or 46.4%). Chi square test showed no significant relationship between proteinuria level and LN histopathological class (p=0.069) nor between age and LN histopathological class (p=0.202). It was concluded that LN patients at Sanglah Hospital in 2016-2020 were mostly women, aged 26-35 years, with a proteinuria level of +3 and included class IV LN. Since there is no correlation between age or proteinuria level with histopathological class, it is recommended that histopathological biopsy be performed in all cases of suspected LN so that patients receive adequate therapy based on the level of kidney damage. Keywords : Lupus nephritis, age, gender, proteinuria level, histopathological class according to ISN/RPS